Effect of Temperature and Ground water on VHF Radio Wave Propagation in Tropical Climate. - SULEMAN Kamaldeen Olasunkanmi (My University, 2017)
Radio-wave propagation is the study of how radio waves travel through a medium from one point to another. Ultra-high Frequency (UHF) and Very High Frequency (VHF) signals are easily reflected by substances and can also be absorbed by some environmental factors such as relative humidity, wind, air and ground temperature, and vegetation. In this paper we present the results of the experimental investigation of the effect of Ground Temperature and Ground Moisture content ratio on the Very High Frequency (VHF) radio wave propagation in wet tropical climate. The data obtained by the experimental method were analysed by 2D-line plotting using originLab software. The results indicate that with the increase in ground temperature, there is a relative increase in the path loss of the radio wave propagation. The inconsistency in the path loss values is due to effect of other climate and environmental factors that can cause distortion of the radio wave. An inverse relationship between the path loss and the relative humidity was obtained from the plot. That is, a decrease in relative humidity brings about a slight increase in path loss. A lower ground moisture ratio brings about a lower path loss because ground moisture increases the conductivity of the soil which allows for better propagation of the surface wave and the results also show that ground moisture has minimal effect on the value of the signal path loss.
Keywords: Ground; Moisture; Attenuation; signal path loss; relative humidity; VHF